Religious education as opening the hermeneutical space - Pollefeyt, Didier (Journal of Religious Education, 2020)
A hermeneutic‐communicative model of religious education is proposed which is grounded in a Christian anthropology. The human person is presented as a 'fragile hermeneutical space'—consisting of a radical openness to reality, an essential indeterminateness and an ability to transcend his or her own reality. This means that people have an inbuilt capacity for receiving meaning. One of the tasks of religious education is to allow children and young people to discover this hermeneutical space within themselves and others. The radical openness of the human person to God is discussed, as are the deficiencies of mono-correlational pedagogies in a pluralised context and the importance of teachers having something to say about the Christian tradition and the way they have integrated it in their own lives.